2023
DOI: 10.3390/agronomy13082120
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Accuracy Evaluation of Cotton Leaf Chlorophyll Content Prediction Model Combined with Hyperspectral Image and Feature Variable Selection

Abstract: In order to explore the feasibility of rapid non-destructive detection of cotton leaf chlorophyll content during the growth stage, this study utilized hyperspectral technology combined with a feature variable selection method to conduct quantitative detection research. Through correlation spectroscopy (COS), a total of 882 representative samples from the seedling stage, bud stage, and flowering and boll stage were used for feature wavelength screening, resulting in 213 selected feature wavelengths. Based on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…When the RPD value was greater than 2, it indicated that the model had high s bility. In addition, each model was run 50 times; the optimal result was selected from the results [42]. Data processing was performed in Matlab R2021b (The MathWorks, Nati MA, USA) and Python 3.11 (Python Software Foundation, Wilmington, DE, USA).…”
Section: Establishment and Assessment Of Modelsmentioning
confidence: 99%
“…When the RPD value was greater than 2, it indicated that the model had high s bility. In addition, each model was run 50 times; the optimal result was selected from the results [42]. Data processing was performed in Matlab R2021b (The MathWorks, Nati MA, USA) and Python 3.11 (Python Software Foundation, Wilmington, DE, USA).…”
Section: Establishment and Assessment Of Modelsmentioning
confidence: 99%